TV white space communications and networks - Stewart, Robert; Crawford, David; Stirling, Andrew (Woodhead Publishing, 2018)
TV White Space Communications and Networks summarizes the current state-of-the-art in this important aspect of wireless communication. Part One covers related technologies, while Part Two looks at policy, regulation and standardization issues. Part Three discusses the commercialization and potential applications of white space networks, rounding out a comprehensive book that provides a standard reference for those researching and commercializing white space networks.--Provided by publisher.